2020
DOI: 10.1021/acs.nanolett.0c03331
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Effects of Environmental Conditions on the Propagation of Respiratory Droplets

Abstract: As coronavirus disease 2019 (COVID-19) continues to spread, a detailed understanding on the transmission mechanisms is of paramount importance. The disease transmits mainly through respiratory droplets and aerosol. Although models for the evaporation and trajectory of respiratory droplets have been developed, how the environment impacts the transmission of COVID-19 is still unclear. In this study, we investigate the propagation of respiratory droplets and aerosol particles generated by speech under a wide rang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 59 publications
(116 reference statements)
0
73
0
Order By: Relevance
“…These droplets are thought to be the main mode of transmission of COVID-19 (1), and they typically travel 1 to 2 m before landing on surrounding surfaces. However, they may be propelled further in the presence of ventilation (2) or forceful ejection (e.g., a violent sneeze) (3) and under certain environmental conditions (e.g., cool and humid) (4). The SARS-CoV-2 virus is also thought to be transmitted by direct contact person to person (e.g., exchange of saliva or a handshake) or by indirect contact through intermediate objects (e.g., sharing of cups, doorknobs).…”
Section: What Is the Difference Between Droplet And Airborne Transmismentioning
confidence: 99%
“…These droplets are thought to be the main mode of transmission of COVID-19 (1), and they typically travel 1 to 2 m before landing on surrounding surfaces. However, they may be propelled further in the presence of ventilation (2) or forceful ejection (e.g., a violent sneeze) (3) and under certain environmental conditions (e.g., cool and humid) (4). The SARS-CoV-2 virus is also thought to be transmitted by direct contact person to person (e.g., exchange of saliva or a handshake) or by indirect contact through intermediate objects (e.g., sharing of cups, doorknobs).…”
Section: What Is the Difference Between Droplet And Airborne Transmismentioning
confidence: 99%
“…Second, longer sunlight exposure and higher outdoor temperature have also been associated with greater extent of viral inactivation (18, 19). Finally, reliable evidence has been provided that virus-containing droplets could travel 3-fold slower in higher temperature environments (20), thus consistently mitigating their air propagation and infective potential.…”
Section: Discussionmentioning
confidence: 99%
“…Background airspeed seems to be another important determinant of infectious disease transmission. Although it is quite understandable that viral-containing aerosols and droplets may propagate over longer distances as the airflow speed increases, it has also been demonstrated that higher air velocity may effectively dilute the number of infectious viral-containing particles (7, 20). In keeping with this theory, a decreased wind speed has been inversely associated with the number of COVID-19 cases in five major Saudi Arabian cities (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People may also become infected through physical contact of virus-contaminated objects such as solid waste ( Al Huraimel et al, 2020 , Ben-Shmuel et al, 2020 , Suman et al, 2020 ). Aerosol transmission in a relatively closed environment ( Azuma et al, 2020 , Zhao et al, 2020 , Tung et al, 2021 ), such as hospital locals have been confirmed ( Shi et al, 2020 ). In addition, environmental pollution caused by feces and urine aerosols ( Heller et al, 2020 ) or physical contact in toilets ( Hoseinzadeh et al, 2020 , Mehraeen et al, 2020 , Pamplona et al, 2020 ) could pose a major transmission risk.…”
Section: Introductionmentioning
confidence: 97%